MSEC Scheme for Providing Secure Data Transformation Using Coding Technique - Kumar.J, Ram; Avutu, Veena; V, Anurag (International Journal of Engineering and Technology, 2018)
The MSEC which is the short from of Multiple Signature Elliptic curve Algorithm by using coding tchnique. It can be Digital Signature Algorithm (DSA) elliptic curve analogue. In 1999, the acknowledgement done such as standard of the ANSI. After that in 2000, it again acknowledged like benchmarks of the IEEE as well as NIST. Like this it again acknowledged in the year 1998 in the name of standard of ISO, as well as it was under thought to incorporate in some of other principles of ISO. unlike logarithm of standard discrete problem as well as number of issues of factorization, none of the  calculation of the sub exponential-time can called  to issue of the elliptic bend discrete logarithm. Similarly per-keybit quality can be generously much prominent  if consider the calculation which uses bends of  elliptic. This implemented system if or  executing the ANSI X9.62 ECDSA  on the bend of elliptic P-192, as well as talking regarding the relevant V of the security. Classes A as well as Subject D.4.6v Descriptors  which is Operating Systems: Security as well as Protection – getting  for  controlling, control of the confirmation cryptographic; E.3 [Data]:cryptosystem of the Data Encryption which is the Public key and standards. Algorithms, of the General Terms Security.